Comparing the impact of an icon array versus a bar graph on preference and understanding of risk information: Results from an online, randomized study - Scalia, Peter; Schubbe, Danielle C.; Lu, Emily S.; Durand, Marie-Anne; Frascara, Jorge; Noel, Guillermina; O’Malley, A. James; Elwyn, Glyn (PloS one, 2021)
Few studies have examined the best way to convey the probability of serious events occurring in the future (i.e., risk of stroke or death) to persons with low numeracy or graph literacy proficiency. To address this gap, we developed and user-tested a bar graph and compared it to icon arrays to assess its impact on understanding and preference for viewing risk information. To determine the: (i) formats' impact on participants' understanding of risk information; (ii) formats' impact on understanding and format preference across numeracy and graph literacy subgroups; (iii) rationale supporting participants' preference for each graphical display format. An online sample (evenly made up of participants with high and low objective numeracy and graph literacy) was randomized to view either the icon array or the bar graph. Each format conveyed the risk of major stroke and death five years after choosing surgery, a stent, or medication to treat carotid artery stenosis. Participants answered questions to assess their understanding of the risk information. Lastly, both formats were presented in parallel, and participants were asked to identify their preferred format to view risk information and explain their preference. Of the 407 participants, 197 were assigned the icon array and 210 the bar graph. Understanding of risk information and format preference did not differ significantly between the two trial arms, irrespective of numeracy and graph literacy proficiency. High numeracy and graph literacy proficiency was associated with high understanding (p<0.01) and a preference for the bar graph (p = 0.01). We found no evidence to demonstrate the superiority of one format over another on understanding. The majority of participants preferred viewing the risk information using the bar graph format.